2020
DOI: 10.20473/iabj.v1i2.35
|View full text |Cite
|
Sign up to set email alerts
|

Computer Assisted Sperm Analysis: A Review

Abstract: Background: A semen analysis exam is a routine check that is done to evaluate fertility. The World Health Organization (WHO) recommended a manual method to obtain objective and standardized values. However, sometimes some errors can be found with this method such as motility. Computer-Assisted Sperm Analysis offers a way to reduce inaccuracies that often occur with manual methods. Reviews:  CASA systems consist of a microscope which connected into a camera to detect microscopic sperm suspension images an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In this study, VCL values >100 µm/s reached the optimal value according to Oliveira et al (2013). According to Agustinus & Pakpahan (2020), VCL is the velocity of sperm on their trajectory and indicates the movement's strength. Moreover, VCL only provides information about the strength of sperm movement but not the course and direction.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In this study, VCL values >100 µm/s reached the optimal value according to Oliveira et al (2013). According to Agustinus & Pakpahan (2020), VCL is the velocity of sperm on their trajectory and indicates the movement's strength. Moreover, VCL only provides information about the strength of sperm movement but not the course and direction.…”
Section: Discussionmentioning
confidence: 60%
“…These results were consistent with the result reported by Ramírez-Reveco et al (2016) that an LDA value of 2-3 µm. Agustinus & Pakpahan (2020) found that the LDA value between trials depended on many factors, including CASA type, standard sperm trajectory, and device setting.…”
Section: Discussionmentioning
confidence: 99%
“…He/she should keep the temperature of the semen, perform seminal plasma examination, homogenize the sample well prior to examination, and cross check the result before it's printed. 3…”
Section: Computer Assisted Sperm Analysis (Casa)mentioning
confidence: 99%
“…The product used is CASA (Computer-Aided Sperm Analysis) or sperm analyzer [17]. With CASA [18], microscopic photographs of semen are taken, as well as analyzing the number, movement, and morphology of sperm in the semen [19]. Despite its capabilities, commercial CASA products are too expensive and rudimentary [20].…”
Section: Introductionmentioning
confidence: 99%